Significance of Conclusions of Deontological Forensic Examination in Lithuanian Criminal Procedure - Šivickaitė-Moldarienė, Laura (Teisė, 2021)
Definition and regulation of forensic deontological examination are presented in the article. The presumption that the expert becomes scientific judge in cases related to mistakes of physicians is defended basing it on forensic and court practices.